ANTIMICROBIAL ACTIVITIES OF LANTANA CAMARA LINN. - K, GIRISH (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Herbal drugs are the potential sources of therapeutic aid for the treatment and prevention of number of ailments as recognized very early by Ayurveda, Unani, and traditional folk - medical practitioners. The rich biodiversity of plants makes them a treasure house for obtaining new and novel compounds either themselves as drugs or lead molecules for drugs with different mechanisms of action. Lantana camara L. belonging to the family Verbenaceae and universally known as wild or red sage is the most widespread species of the genus. It occurs in most parts of the world as an evergreen notorious weed species. It is also considered as an ornamental garden plant. It is widely used in different traditional medical practices for treating various health problems. Different parts of the plant are used in treating various human ailments. The plant extracts and essential oil of L. camara possess various bioactivities including antimicrobial activities. The therapeutic potential of the plant is due to the occurrence of many bioactive phytocompounds. In last decade, scientists and researchers around the globe have elaborately studied the chemical composition of the whole plant of L. camara as well as its biological activities. This article reviews the antimicrobial activities of L. camara. Keywords: Antimicrobial activities, Essential oils, Nanoparticles, Lantana camara, Solvent extracts.